The Farmers’ Satisfaction of UPJA Services in Yogyakarta - Temy Indrayanti; Adi Prayoga; Irwanto; Kemal Mahfud (Jurnal Ilmu Pertanian Indonesia, 2025)
Agricultural Equipment and Machinery Services Business (UPJA) is a rural economic entity that provides services to improve farming equipment and machinery (alsintan). UPJA's good performance will satisfy consumers (farmers). The purpose of this survey was to discover how satisfied farmers were with UPJA services. The method employed was descriptive, with IPA-Kano integrated analysis. The data was gathered through interviews and the distribution of questionnaires to 90 UPJA clients from three classes: Beginner, Developing, and Professional. The results revealed that clients were Quite Satisfied in the Beginner class, Very Satisfied in the Developing class, and Satisfied in the Professional class. The Beginner class's priorities for increasing service were the diversity of machinery, its adequacy, and the number of staff. In the Developing and Professional classes, advertising attributes, personal protective equipment utilization, and team member uniforms were prioritized for service improvement. Keywords: agricultural tools and machinery, farmers’ satisfaction, UPJA